2011
DOI: 10.14311/1332
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy of the Stellar Wind in the Cygnus X-1 System

Abstract: The X-ray luminosity of black holes is produced through the accretion of material from their companion stars. Depending on the mass of the donor star, accretion of the material falling onto the black hole through the inner Lagrange point of the system or accretion by the strong stellar wind can occur. Cygnus X-1 is a high mass X-ray binary system, where the black hole is powered by accretion of the stellar wind of its supergiant companion star HDE226868. As the companion is close to filling its Roche lobe, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In addition to the general change in spectral shape due to photoelectric absorption, we see strong changes between the individual dipping stages in the region between 1.6 keV and 2.7 keV (7.7-4.6 Å), where absorption lines of silicon and sulfur ions are the most prominent spectral features (box in Fig. 4, see also Miškovičová et al 2011). We therefore concentrate on these Si and S lines.…”
Section: Spectral Evolution From Non-dip To Dipmentioning
confidence: 78%
See 1 more Smart Citation
“…In addition to the general change in spectral shape due to photoelectric absorption, we see strong changes between the individual dipping stages in the region between 1.6 keV and 2.7 keV (7.7-4.6 Å), where absorption lines of silicon and sulfur ions are the most prominent spectral features (box in Fig. 4, see also Miškovičová et al 2011). We therefore concentrate on these Si and S lines.…”
Section: Spectral Evolution From Non-dip To Dipmentioning
confidence: 78%
“…Clear P Cygni-like profiles for Cyg X-1 were reported only at φ orb = 0.5 during ObsID 11044 (Miškovičová et al 2011). Schulz et al (2002b) also found indications of P Cygni profiles at φ orb = 0.74.…”
Section: Line Symmetrymentioning
confidence: 87%
“…H-and He-like, ions (Hanke et al 2009, Miškovičová et al 2012, in the case of silicon and, with lower signal to noise, sulfur those lines grow significantly weaker with increasing dipping strength. Instead, 1s-2p transitions of low charge states (Li-through N-like) of the same elements appear, indicating a shift of the charge balance of the observed spectra toward low ionization states (Miškovičová et al 2011(Miškovičová et al , 2012. The latter can only be in equilibrium with the radiation field, if they exist in correspondingly dense clumps of material.…”
Section: Introductionmentioning
confidence: 99%